2013
DOI: 10.1097/jto.0b013e3182773fce
|View full text |Cite
|
Sign up to set email alerts
|

Symptom and Quality of Life Benefit of Afatinib in Advanced Non–Small-Cell Lung Cancer Patients Previously Treated with Erlotinib or Gefitinib: Results of a Randomized Phase IIb/III Trial (LUX-Lung 1)

Abstract: In the LUX-Lung 1 trial, the addition of afatinib to BSC significantly improved non-small-cell lung cancer-related symptoms (cough, dyspnea, and pain), fatigue, physical functioning, and HRQoL and significantly delayed time to deterioration of cough.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 21 publications
0
55
0
3
Order By: Relevance
“…250 Erlotinib, gefitinib, or afatinib may be continued in patients with sensitizing EGFR mutations whose disease has progressed after first-line therapy. 15,[218][219][220] Osimertinib is recommended for patients with T790M whose disease becomes resistant to erlotinib, afatinib, or gefitinib. 39 Afatinib/cetuximab may be considered for patients with sensitizing EGFR mutations whose disease has progressed after EGFR TKI therapy and chemotherapy.…”
Section: Second-line and Beyond (Subsequent) Systemic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…250 Erlotinib, gefitinib, or afatinib may be continued in patients with sensitizing EGFR mutations whose disease has progressed after first-line therapy. 15,[218][219][220] Osimertinib is recommended for patients with T790M whose disease becomes resistant to erlotinib, afatinib, or gefitinib. 39 Afatinib/cetuximab may be considered for patients with sensitizing EGFR mutations whose disease has progressed after EGFR TKI therapy and chemotherapy.…”
Section: Second-line and Beyond (Subsequent) Systemic Therapymentioning
confidence: 99%
“…[214][215][216][217] The NCCN panel recommends continuing erlotinib, gefitinib, or afatinib and considering local therapy in patients with asymptomatic progression; however, treatment varies for patients with symptomatic progression (see NSCL-19, page 508). [218][219][220] For the 2017 updates (Versions 1 and 4), the NCCN panel revised the recommendations for patients with sensitizing EGFR mutations whose disease has progressed on erlotinib, gefitinib, or afatinib. Osimertinib is now recommended (category 1) for patients with symptomatic brain metastases.…”
Section: Continuation Of Erlotinib Gefitinib or Afatinib After Progmentioning
confidence: 99%
“…Finally, results of the LUX-Lung 1 study showed significantly improved global qol, physical function, and fatigue with afatinib use. In addition, afatinib also improved lung cancer-related symptoms such as cough, dyspnea, and pain, and significantly delayed time to deterioration 50 .…”
Section: Benefits Of Egfr-tkismentioning
confidence: 99%
“…A phase iib/iii study (LUX-Lung 1) in patients failing chemotherapy and erlotinib or gefitinib found a tripling in median pfs to 3.3 months from 1.1 month (hr: 0.38; p < 0.0001) with the addition of afatinib (50 mg) to best supportive care 50 (Table iii). In addition, a subgroup analysis examined the benefit of afatinib in patients with the highest likelihood of EGFR mutations-that is, those with a complete or partial response on prior erlotinib or gefitinib, or with 48 weeks or more on treatment with erlotinib or gefitinib, or both 51 .…”
Section: Pretreated Patientsmentioning
confidence: 99%
“…Indeed 79% and 68% of patients in the placebo and afatinib arms, respectively, received additional treatment. Afatinib treatment in LUX-Lung 1 was also associated with significant improvement in NSCLCrelated symptoms and quality of life (QoL; P 6 0.05) [72]. In the first-line setting, the clinical activity of afatinib was assessed in the proof-of-concept, Phase II LUX-Lung 2 study, which enrolled 129 patients with EGFR-mutation-positive NSCLC (>80% with Del19 or L858R mutations) [ [74].…”
Section: Pelitinib Av-412/mp-412 and Bms-599626mentioning
confidence: 99%